Finger Tracker Untuk Penerjemahan Bahasa Isyarat Angka 1-10 Untuk Tunawicara Menggunakan Webcam Dengan Metode Centroid - Cici Ardianti; Azhar Al Havis; Munawir Munawir (Fakultas Informatika, 2018)
Visual sensing or machine vision is a process of image data manipulation. The data can be used to interpret many things, one of which is the introduction of gesture. Gesture recognition is an interface that can recognize the gestures of a human being and translate these movements as instructions that can be understood by a computer. Gesture recognition can be used to translate sign language into speech people. This is because there are many people who do not understand the language of the hands of the speechless. So, people with disabilities have difficulty interacting in society. In this final assignment the introduction of gesture for the translation of sign language leads more to hand recognition, namely the detection of changes in hand motion, by using a laptop as its device. Laptops have cameras to capture the image of people who are speechless when communicating using sign language in the form of hand movements. Furthermore, the image is processed by the laptop processing unit to carry out the process of hand recognition. After the process is complete, the display screen will display the number of changes in the position of the hand movements performed by the speech person in front of the camera.